Malnutrition diagnosed by the Global Leadership Initiative on Malnutrition criteria as a predictor of gait ability in patients with hip fracture. Issue 10 (October 2022) - Kobayashi, Hikaru; Inoue, Tatsuro; Ogawa, Masato; Abe, Takafumi; Tanaka, Toshiaki; Kakiuchi, Masayoshi
Highlights: GLIM and ESPEN criteria diagnosed malnutrition in 73.9% and 25.5% patients, respectively. Malnutrition diagnosed by GLIM predicts lower gait ability at discharge. Reduced muscle mass in components of the GLIM criteria predicts lower gait ability. Abstract: Aim: Malnutrition is common in patients with hip fractures and is associated with poor clinical outcomes. The Global Leadership Initiative on Malnutrition (GLIM) and the European Society for Clinical Nutrition and Metabolism (ESPEN) criteria are widely used to diagnose malnutrition. However, the criteria regarding the prediction of gait ability in patients with hip fractures during the acute phase remain unclear. We aimed to determine whether GLIM or ESPEN criteria were more appropriate for predicting gait ability at discharge from an acute hospital. Methods: This retrospective observational study included hip fracture patients aged ≥ 65 years. Patients were classified as malnourished or non-malnourished according to the GLIM and ESPEN criteria at admission. The primary outcome was gait ability, which was evaluated using functional ambulation categories (FAC) at discharge. We categorized into those with (FAC score ≥ 3 points) and without (< 3 points) improved gait ability. Logistic regression analysis for FAC was performed to determine whether GLIM or ESPEN was predictive of gait ability at discharge. Results: Overall 157 patients were included; the median age was 84 years, and 75.3% were female. The prevalence of malnutrition was 73.9% and 25.5% according to the GLIM and ESPEN criteria, respectively. Logistic regression analysis showed that malnutrition evaluated using the GLIM criteria were predictive of lower FAC at discharge (odds ratio, 0.394; 95% CI, 0.164–0.946), while ESPEN criteria did not show statistically significant differences (odds ratio, 0.625; 95% CI, 0.292–1.335). Conclusion: GLIM criteria are useful for predicting gait ability at discharge during acute hospitalization in patients with hip fractures.